2009
DOI: 10.1007/978-1-60761-585-9_11
|View full text |Cite
|
Sign up to set email alerts
|

NKT Cell Responses to Glycolipid Activation

Abstract: NKT cells are a distinct lineage of T lymphocytes that are usually identified by the co-expression of the semi-invariant CD1d-restricted alphabeta TCR and the NK1.1 allelic marker of NK lineage receptors in the C57BL/6 mice and related strains. NKT cells can be subdivided based on CD4/CD8 expression and on tissue of origin. NKT cells express significantly the TCR gene products Valpha24 JalphaQ in humans, the homolog of mouse Valpha14 Jalpha18, paired with Vbeta11, the homolog of mouse Vbeta8.2. NKT cells are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In addition, we found that Th2 cytokine like IL-4 and IL-13, most of which may serve in protecting the intestine from inflammation, was increased in DSS/7DW-8 group. 5 Our opinion regarding this finding is that even though an accumulation of CD1d-restricted NKT cells occurred in the DSS/7DW8-5 group, these cells still represented a small population in the whole colon tissue. Thus, the absolute level of cytokines derived from NKT cells represents only a limited amount of the total RNA samples and could be below the cutoff threshold value.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, we found that Th2 cytokine like IL-4 and IL-13, most of which may serve in protecting the intestine from inflammation, was increased in DSS/7DW-8 group. 5 Our opinion regarding this finding is that even though an accumulation of CD1d-restricted NKT cells occurred in the DSS/7DW8-5 group, these cells still represented a small population in the whole colon tissue. Thus, the absolute level of cytokines derived from NKT cells represents only a limited amount of the total RNA samples and could be below the cutoff threshold value.…”
Section: Discussionmentioning
confidence: 83%
“…13,[21][22][23][24] 7DW8-5 is a biologically more potent analog of α-GalCer 12 and is viewed as a promising immunotherapeutic agent, especially as a potential vaccine adjuvant for malaria, HIV, and tuberculosis. 12,13,18 Previous reports have indicated that α-GalCer ameliorates the intestinal inflammation induced by DSS; 10 however, 7DW8- 5 has not yet been evaluated for its effects on intestinal inflammation. In the present study, we demonstrated that 7DW8-5 activates CD1d-restricted NKT cells through CD1d and provides a protective effect against intestinal inflammation in mice.…”
Section: Discussionmentioning
confidence: 99%
“…To this aim, we incubated human PBMC with simplexide (100 nM) or α-GalCer (100 nM) in the presence of IL-2 (100 U/ml) [38]. After 7 days, the percentage of CD3 + Vα24 + cells was assessed by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…NK cells also interact with immature DCs or autoreactive T cells to maintain immune homeostasis [ 35 ]. Previous work revealed that the liver's microenvironment influences the unique phenotype and development of liver NK cell subsets [ 36 ]. NK cell receptors can become phenotypically modified so as to promote high levels of the inhibitory receptor NKG2A, while losing expression of MHC class I-binding Ly49 receptors, thus sustaining the functional hyporesponsive status of NK cells.…”
Section: Nk Cell Distribution and Liver Microenvironmentmentioning
confidence: 99%